Governing the ungovernable recontextualizations of "competition" in European policy discourse - Laura Porak (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
The role of the state and political authorities has always been highly ambivalent in different strands of neoliberalism. This paper aims to highlight contradictory political stances towards competition and associated modes of governance by analyzing policy discourse of the European Commission. While economic knowledge gained social relevance over the last decades, economic theory and thus also competition is characterized by its polysemy. Hence, different strands of economic thought are based on different 'economic imaginaries'. By conducting a Critical Discourse Analysis of the most recent 'governance structure' of the EU, 'Europe 2020', I found that competition is naturalized as mode of economic organization. The main contribution of this paper is the reconstruction of two 'economic imaginaries'. First, the European Commission as political sovereign and second, as an actor in the (world) market. Each 'economic imaginary' has distinct ideas about the functioning of the economy and the role of the political sovereign. Hence, they also have different policy implications. Moreover, I identify five discursive strategies employed to legitimize contradictory stances towards (the governance) of competition. Both the 'economic imaginaries' and the discursive strategies are clearly indicating a strong neoliberal influence on the 'governance structure' 'Europe 2020'.
Keywords: 330; Critical Discourse Analysis; European Commission; Europe 2020; Performativity of Economics; Competition; Competitiveness